Design of Electronic Blood Pressure Testing System. (September 2020) - Feng, Chenwei; Liu, Caifu; Zou, Ziliang; Deng, Mingyu; Hong, Yanjun
Abstract: With the continuous development of electronic technology, the previous traditional methods of blood pressure testing are far from meeting people's requirements. Fortunately, the advent of electronic blood pressure meters has shown great convenience and potential. Against the backdrop, a new electric blood pressure testing system based on a CC3200 LaunchPad is proposed in this paper, which uses a pressure sensor to collect the information of static pressure and fluctuation of blood pressure, and then transmits the processed data to the software in PC. The software in PC analyzes the data by oscillometric method and Gaussian fitting method, and then the static pressure, systolic pressure and diastolic pressure are calculated and displayed. Test results show that the blood pressure testing efficiency is greatly improved by this system with its high accuracy and reliability, which can meet the requirement of the AAMI (Association for the Advancement of Medical Instrumentation) standard.